2016
DOI: 10.2337/db15-1725
|View full text |Cite
|
Sign up to set email alerts
|

Mfn1 Deficiency in the Liver Protects Against Diet-Induced Insulin Resistance and Enhances the Hypoglycemic Effect of Metformin

Abstract: Mitochondrial function can be influenced by mitochondrial shape and connectivity with other cellular organelles through fusion and fission processes. Disturbances in mitochondrial architecture and mitochondrial fusion-related genes are observed in situations of type 2 diabetes and obesity, leading to a highly fissioned mitochondrial network. To directly test the effect of reduced mitochondrial fusion on hepatic metabolism, we generated mice with a liver-specific deletion of the Mfn1 gene (Mfn1LKO) and monitore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
56
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 79 publications
(65 citation statements)
references
References 39 publications
3
56
1
Order By: Relevance
“…Mfn1 is an essential protein for mitochondria fusion events. Accordingly, decreased Mfn1 function has been shown to trigger a profound shift in the fusion/fission balance, toward a dramatically fragmented mitochondrial network in most, if not all, cells and tissues tested to date (Chen et al , 2003; Park et al , 2008; Papanicolaou et al , 2012; Dietrich et al , 2013; Kulkarni et al , 2016). Further, While Mfn1 mRNA levels did not compensate for Mfn2 loss, we observed that Mfn1 protein slightly decreased in the BAT and WAT form Mfn2‐adKO mice (Fig EV1A).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Mfn1 is an essential protein for mitochondria fusion events. Accordingly, decreased Mfn1 function has been shown to trigger a profound shift in the fusion/fission balance, toward a dramatically fragmented mitochondrial network in most, if not all, cells and tissues tested to date (Chen et al , 2003; Park et al , 2008; Papanicolaou et al , 2012; Dietrich et al , 2013; Kulkarni et al , 2016). Further, While Mfn1 mRNA levels did not compensate for Mfn2 loss, we observed that Mfn1 protein slightly decreased in the BAT and WAT form Mfn2‐adKO mice (Fig EV1A).…”
Section: Resultsmentioning
confidence: 99%
“…The values obtained with Ama were substracted, and the relative increases in O 2 consumption triggered by CL were measured respective to basal respiration for each adipocyte preparation. Respirometry analyses in isolated mitochondria were performed as recently described (Kulkarni et al , 2016). …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Targeting liver specific MFN1 has been shown to induce a metabolic switch from glucose to lipid metabolism, enhance respiratory capacity, and offer protection against insulin‐resistance in a high fat diet (HFD) induced obese mice model. [ 70 ] Interestingly, loss of MFN1 in the liver enhances hypoglycemic activity of Metformin by increasing AMPK activity. Hypothalamic Proopiomelanocortin neurons play a major role in regulating food intake, nutrient sensing, energy expenditure, and metabolic adaptations.…”
Section: Dysfunctional Fission and Fusion Proteins In Agingmentioning
confidence: 99%